2014
DOI: 10.1007/s10529-013-1435-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of riboflavin biosynthesis in Bacillus subtilis under production conditions

Abstract: To study the network dynamics of the riboflavin biosynthesis pathway and to identify potential bottlenecks in the system, an ordinary differential equation-based model was constructed using available literature data for production strains. The results confirmed that the RibA protein is rate limiting in the pathway. Under the conditions investigated, we determined a potential limiting order of the remaining enzymes under increased RibA concentration (>0.102 mM) and therefore higher riboflavin production (>0.045… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…These results confirm a previous study [32] where it was shown that when an excess of GTP and ribulose-5-phosphate are found in culture media, the ribA gene was overexpressed as were the enzymes, GTP cyclohydrolase II, and DHBP synthase, coding by this gene. These same authors also showed that under these conditions, the enzymes coded by FIGURE 3 Comparison of the relative expression levels of rib genes of L. plantarum CRL 725 between late-exponential-phase-cells growing in SSDM and late-exponential-phase-cells growing in SSM at 30°C.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm a previous study [32] where it was shown that when an excess of GTP and ribulose-5-phosphate are found in culture media, the ribA gene was overexpressed as were the enzymes, GTP cyclohydrolase II, and DHBP synthase, coding by this gene. These same authors also showed that under these conditions, the enzymes coded by FIGURE 3 Comparison of the relative expression levels of rib genes of L. plantarum CRL 725 between late-exponential-phase-cells growing in SSDM and late-exponential-phase-cells growing in SSM at 30°C.…”
Section: Discussionsupporting
confidence: 92%
“…These results confirm a previous study where it was shown that when an excess of GTP and ribulose‐5‐phosphate are found in culture media, the ribA gene was overexpressed as were the enzymes, GTP cyclohydrolase II, and DHBP synthase, coding by this gene. These same authors also showed that under these conditions, the enzymes coded by ribH (lumazine synthase) and ribG (deaminase and reductase) were not modified, suggesting that they are not affected by external nutrients sources and would constitute non‐modifiable bottleneck steps in riboflavin biosynthesis.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the mean values given above, the GTP cyclohydrolase II reaction, and therefore the bifunctional RibA protein of B. subtilis, exhibits the largest average control over the riboflavin synthase flux (mean values of C vnet;7 e 1 and C vnet;7 e RibA are 0.45 and 0.55, respectively). This finding is consistent with our previously published in silico kinetic study [61]. Regarding the experimental findings, it appears that GTP cyclohydrolase II has a special limiting influence on riboflavin production in recombinant bacterial overproducer strains.…”
Section: Probabilistic Metabolic Control Analysissupporting
confidence: 93%
“…Here, we used the convenience rate law to describe the enzyme kinetics because detailed in vivo enzymatic rate laws with respect to reactants and products are not available [61]. The convenience rate law is a heuristic approximate enzyme kinetic rate law that is used in models of biochemical reaction networks with plausible biological properties [22,29,60].…”
Section: Probabilistic Metabolic Control Analysismentioning
confidence: 99%
See 1 more Smart Citation